2018
DOI: 10.1159/000489634
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Mebicar and Ginsenoside Rg1 on Neurobehavioral and Immunological Disruptions Caused by Intermittent Unpredictable Stress in Mice

Abstract: Objectives: Ginsenoside Rg1 and mebicar have been reported to have broad efficacy spectrum, including anti-anxiety and anti-stress. These drugs have been used not only for treatment but also for the purpose of increasing resistance from disease. A specific aim of this study was to investigate whether mebicar or ginsenoside Rg1 can prevent physiological changes resulting from intermittent unpredictable stress (IUS). Methods: Seven week-old Balb/cByJ mice were administered orally with mebicar (10 mg/kg) or ginse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The results indicated that the components identified here were mostly ginsenosides. As previously stated, ginsenosides such as Re, Rg 1 , Rf, Ro, Rc, Rb 1 , Rb 2 , and Rb 3 have a broad range of pharmacological and health effects, including antinociceptive [6], anti‐inflammatory [41], antidiabetic [42], cardiovascular [43], anti‐breast carcinoma [44], liver protective [45], anti‐stress [46], and anticancer effects [47]. The findings demonstrated that the majority of ginsenosides had a positive correlation with the increasing age of MCG, implying that high‐aged MCG has superior pharmacological effects and health benefits.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the components identified here were mostly ginsenosides. As previously stated, ginsenosides such as Re, Rg 1 , Rf, Ro, Rc, Rb 1 , Rb 2 , and Rb 3 have a broad range of pharmacological and health effects, including antinociceptive [6], anti‐inflammatory [41], antidiabetic [42], cardiovascular [43], anti‐breast carcinoma [44], liver protective [45], anti‐stress [46], and anticancer effects [47]. The findings demonstrated that the majority of ginsenosides had a positive correlation with the increasing age of MCG, implying that high‐aged MCG has superior pharmacological effects and health benefits.…”
Section: Resultsmentioning
confidence: 99%
“…26 In addition, ginsenoside has antidepressant effects, 27 prevents cognitive impairment by improving mitochondrial dysfunction in Alzheimer’s Disease (AD), 28 ameliorates memory impairments, 29 and has anti-anxiety and anti-stress properties. 30 Previous animal experiments have suggested that stress stimulation can lead to reduced expression of brain-derived neurotrophic factor (BDNF), and they demonstrated that ginsenoside can effectively upregulate BDNF in the hippocampus, downregulate serum cortisol levels, and reduce or reverse changes in the density of synaptic spine neurons in the hippocampus caused by chronic stress. 31 In addition, abnormal volume and structure of neurons was discovered in the amygdala and hippocampus; 32 ginsenoside could effectively improve these pathological changes.…”
Section: Pharmacological Studies Of the Active Compounds Of Nine Chinmentioning
confidence: 99%